2013
DOI: 10.1371/journal.pone.0081587
|View full text |Cite|
|
Sign up to set email alerts
|

A Truncated Receptor-Binding Domain of MERS-CoV Spike Protein Potently Inhibits MERS-CoV Infection and Induces Strong Neutralizing Antibody Responses: Implication for Developing Therapeutics and Vaccines

Abstract: An emerging respiratory infectious disease with high mortality, Middle East respiratory syndrome (MERS), is caused by a novel coronavirus (MERS-CoV). It was first reported in 2012 in Saudi Arabia and has now spread to eight countries. Development of effective therapeutics and vaccines is crucial to save lives and halt the spread of MERS-CoV. Here, we show that a recombinant protein containing a 212-amino acid fragment (residues 377-588) in the truncated receptor-binding domain (RBD: residues 367–606) of MERS-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
216
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(220 citation statements)
references
References 42 publications
3
216
0
1
Order By: Relevance
“…Type I IFN and ribavirin have been reported to ameliorate disease in infected macaques (15), and small molecules targeting diverse intracellular pathways have been shown to inhibit MERS-CoV in vitro (16)(17)(18). Furthermore, experimental immunogens can elicit an anti-MERS-CoV response (19,20). However, no MERS-CoV targeting therapeutic has been demonstrated to function in vivo, partly because of limited small animal models of infection (21)(22)(23).…”
mentioning
confidence: 99%
“…Type I IFN and ribavirin have been reported to ameliorate disease in infected macaques (15), and small molecules targeting diverse intracellular pathways have been shown to inhibit MERS-CoV in vitro (16)(17)(18). Furthermore, experimental immunogens can elicit an anti-MERS-CoV response (19,20). However, no MERS-CoV targeting therapeutic has been demonstrated to function in vivo, partly because of limited small animal models of infection (21)(22)(23).…”
mentioning
confidence: 99%
“…We have previously demonstrated that the Fc-conjugated RBD-containing H5N1 influenza vaccine induces strong cross-protection (Du et al, 2013c). We have also shown that vaccines based on the RBD of spike proteins of severe acute respiratory syndrome coronavirus and Middle East respiratory syndrome coronavirus elicit highly potent neutralizing antibody responses that protect animals from viral challenges (He et al, 2004;Du et al, 2007Du et al, , 2008Du et al, , 2009Du et al, , 2013aMa et al, 2014;Zhang et al, 2015).…”
Section: H D -F C S T -F C H a E -F C C O N T R O L H D -F C + S T -Fmentioning
confidence: 99%
“…The induction of neutralizing activity by a recombinant protein fragment containing residues 377–662 of MERS-CoV RBD has also been demonstrated. Particularly, a truncated 212-amino acid RBD fragment containing residues 377–588 (inside RBD: residues 367–606) of MERS-CoV S protein induced strong MERS-CoV S-specific antibodies in vaccinated mice, blocking the binding of MERS-CoV RBD to viral receptor DPP4 and effectively neutralizing MERS-CoV infection, thus providing promise for further development as an effective and safe MERS vaccine [5657]. …”
Section: Current Advancements On Mers Vaccine Developmentmentioning
confidence: 99%
“…Since the RBD of SARS-CoV contains multiple neutralizing epitopes, RBD-based SARS subunit vaccines covering these neutralizing epitopes are able to induce potent neutralizing antibodies completely preventing SARS-CoV challenge [50, 51]. Similarly, it has been shown that the RBD of MERS-CoV induced strong neutralizing antibody responses against infection of MERS-CoV [56, 57] and that the MERS-CoV RBD does, indeed, contain several important neutralizing epitopes [93]. Accordingly, further optimization of the RBD and development of optimized RBD-based MERS subunit vaccines containing multiple neutralizing epitopes would be desirable and feasible to improve the vaccine efficacy.…”
Section: Potential Strategies For Developing Mers Vaccinesmentioning
confidence: 99%